Pengaruh Back Rolling Massage dan Akupunktur Titik GB21 terhadap Produksi ASI Ibu Post Partum - Ekadewi Retnosari; Nia Clarasari MP (Politeknik Kesehatan Tanjung Karang, 2021)
Early breastfeeding is an initial key to success in breastfeeding practice where breastmilk is given immediately 3 minutes after birth. Breastfeeding problems can appear, one of them, are caused by certain conditions. For instance, the mother complains on the first day of breast milk production and the ejection of it cannot get out or just a little bit, so it makes a worried the mother in giving breast milk. This is also compounded by the fussy condition of the baby’s which makes mothers think that their breast milk is not enough to fulfill the baby's nutrition. It is no least of mothers who give formula milk to their babies and not to train their babies to suck mother’s nipple. In a worrying condition and lack confidence feeling about insufficient breast milk, a mother needs help and support in producing breast milk. Some of the alternative efforts can be done to increase breast milk production either using pharmacology or non-pharmacology. A way in non-pharmacology is by doing the back rolling massage and acupuncture point GB21. This research was conducted to analyze the influence of back rolling massage and acupuncture point GB21 on breast milk production. The method was a quasi-experiment with pretest-posttest with a control group design; the total sample was 90 post-partum mothers. The result showed there was a significant influence of weight after the research on the three groups (p-value 0,0001). The conclusion that back rolling massage and acupuncture point GB21 give an influence in increasing breast milk production.